2001
DOI: 10.1034/j.1399-302x.2001.160402.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characteristics of antibodies induced by Arg‐gingipain (HRgpA) and Lys‐gingipain (Kgp) from Porphyromonas gingivalis

Abstract: Arginine-specific gingipain (HRgpA) and lysine-specific gingipain (Kgp), enzymes produced by Porphyromonas gingivalis, may be candidates for an anti-P. gingivalis vaccine. The purpose of our study was to determine whether HRgpA and Kgp have opsonic target sites and whether these sites are available and accessible on intact P. gingivalis cells. Rabbits were used to generate polyclonal antibodies to both proteins. Animals were immunized and immunoglobulin G (IgG) fractions were isolated from preimmune and immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 65 publications
1
26
0
1
Order By: Relevance
“…Mice immunized with RgpA polypeptides were protected from P. gingivalis-elicited oral bone loss, with this antigen also eliciting a potent IgG response (Gibson et al, 2001). In addition, IgG against purified RgpA also showed a protective effect, enhancing PMN-mediated bacterial killing of P. gingivalis strains (Nakagawa et al, 2001). When these findings are considered together with the present results, it seems clear that IgG can exert a preventive effect against components of P. gingivalis.…”
Section: Discussionsupporting
confidence: 48%
“…Mice immunized with RgpA polypeptides were protected from P. gingivalis-elicited oral bone loss, with this antigen also eliciting a potent IgG response (Gibson et al, 2001). In addition, IgG against purified RgpA also showed a protective effect, enhancing PMN-mediated bacterial killing of P. gingivalis strains (Nakagawa et al, 2001). When these findings are considered together with the present results, it seems clear that IgG can exert a preventive effect against components of P. gingivalis.…”
Section: Discussionsupporting
confidence: 48%
“…Passive immunization with antibodies from several different species has been used as immunotherapy against dental caries (25,26) and periodontitis (27)(28)(29)(30)(31)(32). Previous studies have shown that antibodies are actively transported to the egg yolk of immunized hens (33).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous results have indicated that the protease mutant forms significantly smaller lesions in mice than does the wild type [24]. Further study is needed to elucidate the role of the activation of PMNs by dentilisin in colonization by T. denticola and inflammation of periodontal tissue.…”
Section: Discussionmentioning
confidence: 99%